A Comparative Study of Ngapsahi Analysis and Tagmemic Analysis on Arabic Texts in Kitab Kuning - Muhamad Jaeni (Arabic Education Program IAIN Pekalongan, 2018)
There are various traditions used in interpreting a book or kitab. One of the models of interpreting kitab kuning used in pesantren is Ngapsahi. This is a creative and effective model using grammatical markers. Actually, the analysis of the grammatical markers has been used by western linguists, although it only emphasizes on the analysis of the structural latin texts, such as English, France, Indonesian, and other latin languages. This analysis model has not been implemented in Arabic texts. Yet, the western linguists believe that this tradition is universal which can be implemented in any language in the world. This study focuses on creating Ngapsahi analysis system and comparing it with Tagmemic analysis in kitab kuning. There are three steps used in the research method including finding data and sources; analyzing the data and the sources; and drawing conclusion. The results of this study are: First, Tagmemic analysis can be implemented in Arabic text inspite of the uncomplete dimensions covered by this analysis. Second, Ngapsahi analysis model is a specific model created by pesantren’s priest. Third, there is a similarity between Tagmemic and Ngapsahi analyses, especially which is in the term of linguistic dimensions (Slot, Class, Role, Cohesion) filled by the grammatical markers. The difference between those analyses is the more complete dimensions of Ngapsahi analysis than Tagmemic’s because of the complexity and compliteness of Arabic text system.